The Influence of Learning Video Media in Developing Media Literacy Capability of Students of Mathematics Education Study Program STKIP Harapan Bima (Universitas PGRI Sumatera Barat, 2023)
Literacy is very important in the 21st century because literacy can help success in learning as stated by Ramdhani, et al (2022). Students' ability to increase literacy is a measure of student success. It is hoped that this research will use learning videos that can help develop students' media literacy skills. This research is a quasi-experimental study with a posttest only control group design. In general, this study consisted of several stages, namely giving treatment, collecting data, interpreting data, and drawing conclusions. Based on the results of the SPPS analysis and discussion, it can be concluded that the use of mathematics learning videos in learning activities is stated to be effective in developing students' media literacy skills